Desempenho de bovinos cruzados e parâmetros qualitativos de músculos maturados - Vieira, Leonardo Dimas do Carmo [UNESP] (2015)
The work were developed in Embrapa Southeast Livestock, São Carlos, SP, and Laboratory of Animal Products, belonging FCAV/Unesp, Campus de Jaboticabal, SP. were used 96 cattle (steers and heifers) of nine genetic groups from the mating of cows : Nelore, ½ Angus + ½ Nelore e ½ Senepol + ½ Nelore with bulls of breeds Canchim, Bonsmara e Brangus. The animals were finished in confinement in individual stalls receiving a diet with 13,1% crude protein and 71,0% total digestible nutrients, until they reach slaughter weight of 17 @ for steers and 16@ for heifers, the consumption were monitored daily by weighing the leftovers. The slaughter was take place in commercial abattoir following the routine slaughter of the same. After rigor mortis were analyzed on carcass traits, and samples of longíssimus dorsi (between 12th and 13th ribs) and triceps brachii was be collected for analysis during. The samples were subjected to different maturation periods (0, 7 and 14 days). After the maturation period determined for each treatment were carried out analysis color, pH, water holding capacity, weight loss by cooking, shear force, collagen, myofibril fragmentation index and fatty acid profile. The experimental design was completely randomized with factorial 9 x 2 (9 crossings x 2 genders) to the data performance and carcass quality and 9 x 2 x 3 (9 crossings x 2 genders x 3 periods of maturation) for data quality for meat cuts separately. Data were subjected to analysis of variance and means compared by Tukey test at 5% significance using the SAS (2002)